SISTEM PENUNJANG KEPUTUSAN DALAM PEMILIHAN CALON KARYAWAN BARU SESUAI KRITERIA DENGAN METODE MULTIFACTOR EVALUATION PROCESS (MFEP) - Fredy Setiawan; Joko Priambodo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
An employee is a person who works for a company for a predetermined time and with a predetermined salary as well. A company is not responsible for providing a variety of traditional employer benefits, including taxes, social security and workers' compensation. Employee recruitment is an important thing for companies to get new employees to occupy a position. In some companies, the process of recruiting new employees is still not done in a professional manner. This is because there is no standardized, systematic method for assessing the eligibility of applicants. Choosing employees is also not easy. There are several requirements that must be met in order for the prospective employee to be well received. Several criteria will be taken into account to carry out this employee recruitment selection process. The Decision Support System is a good method in determining whether employees are eligible or not. The application of a Decision Support System for hiring new employees that was built using the Multi Factor Evaluation Process (MFEP) method. The Multi Factor Evaluation Process (MFEP) method can assist the company in determining who will be selected to become employees in the company. By applying this method, Antara Net ( Antara Net) will be very helpful in assessing prospective employees who will be employed in the company.